Impact of mindfulness on irrigation water consumption - Asthana, Anand N. (Frontiers in Water, 2022)
As two irreversible trends - population growth and climate change advance further, demand for water conservation will increase. Since irrigation is the major source of use (and waste) of freshwater, the professionals in this field will be under pressure to find innovative ways to increase physical irrigation efficiency. Irrigation water management promotes the delivery of water in a quantity that meets the needs of the crop while avoiding runoff and prolonged soil saturation. Water and energy can be conserved by improving application precision and decreasing unused applications. The adoption of water conservation technologies do not always increase the physical irrigation efficiency. Paradoxically, in many cases it may also increase water withdrawal. However, there are non-economic reasons because of which farmers invest their time and effort to reduce wastage of water. Higher irrigation efficiency is likely to depend on behavioural characteristics of the farmer. This research looks at whether mindfulness is one of the characteristics that influences water conservation. It also looks at the mechanism of this effect and the mediating role of environmental concern. It is found that mindfulness has a direct effect as also an indirect effect (through environmental concern) on increase in physical irrigation efficiency. The estimated effect of mindfulness through environmental concern is about two-thirds of the total effect, the remaining one-third of the effect coming directly from mindfulness.